DOMINASI TERHADAP PEREMPUAN YANG DIASOSIASIKAN DENGAN ALAM PADA FILM AVATAR (2009): KAJIAN ECOFEMINISME - mirza fathima jauhar kamalia (Jurnal Lingua Idea, 2016)
Avatar movie (2009) reveals the discourse about the women assossiated with the nature. This study uses Ecofeminism theory to answer the problem above. This study uses qualitative approach added with the discourse analysis method by Sara Mills to look for the subject and object position between the women associated with the the nature and the men in the movie. The data source of this study is Avatar movie by James Cameron supported with the books of the theory used in this study. The results of this study show that this movie always tries to perpetuate the position of the women who naturally have association with the nature that can be seen through the characters of Grace and Neytiri. Grace is described as the scientist who definitely has passion and love towards the nature until she can memorize every type of creature in the planet of Pandora and can understand their feeling well. Neytiri is described as the one who has intimate relation with the nature until she can do something impossible to do with it that the others cannot do. Their “special” ability does not make them has the power towards the others because there are the men who is identified themselves as the subject and identified Grace and Neytiri as the object and mediator to get the power and everything they want.